An Evaluation of Impedance Plethysmography and 125I-Fibrinogen Leg Scanning in Patients following Hip Surgery - Cruickshank, M K; Levine, M N; Hirsh, J; Turpie, A G G; Powers, P; Jay, R; Gent, M (Thrombosis and Haemostasis, 1989)
Venous thromboembolism is a common post-operative complication in patients following hip surgery. 125I-fibrinogen leg scanning and impedance plethysmography (IPG), are often used in the detection of venous thrombi in such patients. Information on the sensitivity and specificity of these non-invasive tests for the diagnosis of venous thrombosis following hip surgery is relevant for both patient management and for choosing the appropriate outcome measure for clinical trials evaluating new prophylactic regimens.We determined the sensitivity and specificity of the IPG alone, the 125I-fibrinogen leg scan alone, as well as the combined use of the two tests from a retrospective analysis of 685 hip surgery patients who participated in clinical trials of anti-thrombotic prophylaxis. These patients were followed prospectively with non-invasive tests. Bilateral venography was attempted either when one or both screening tests became positive or on day 10-14 post-operatively if both screening tests remained negative. Adequate venography was obtained in 1,010 (73.7%) legs and thrombi were identified in 198 (19.6%) legs.The sensitivities of the IPG and leg scanning were 12.9% and 44.6% respectively; the corresponding specificities were 98.1% and 95.0%. The sensitivity of a positive result on one or both screening tests was 49.6% with a specificity of 93.9%.Therefore, leg scanning and IPG, even in combination, are not sufficiently accurate to be recommended as the only strategy for the diagnosis of venous thrombosis following hip surgery. Venography should be considered in all patients undergoing surveillance testing either when one or both of the screening tests become positive or on day 10-14 if the screening tests remain negative.
Keywords: Deep vein thrombosis; Hip surgery; Impedance plethysmography